Impact of Globalization in Higher Education - A Study - N, Gowri Rao; Selvakumar, Y Stanly (Journal of Advanced Research in English & Education, 2022)
Over time, the main drivers of economic growth have varied. Knowledge is now universally recognized as the key to growth. Widening educational options for citizens is a result of educational globalization. Student mobility is one of the most obvious effects of globalization. Across 2.5 million students, numerous researchers, institutions, and universities were reportedly freely traveling around the world in 2000, and it was expected that this figure may increase to 7 million students by 2020 (OECD and UNESCO, Institute for Economics, 2012). In the following years, the PANDEMIC has risen the demands of every stakeholder. It hastens the tech-development as for as the educational sector is concerned. Together with this, Globalization has generally placed more emphasis on decentralized educational governance and control. It has aided in the enhancement of health, education, and living standards as well as the growth of technology, particularly in the field of information technology. The study analyses the effects on education, paying particular emphasis to international education, lifelong learning, educational reform, and potential future changes in design education. The observations and experiences are focused on how to apply a broad theoretical idea to a specific circumstance that includes educational management, course design, pedagogical style, accountability, quality, and accreditation, as well as funding. The study illustrates that future opportunities and developments in all facets of education in the integrated knowledge-driven community will inevitably be based on the international recognition of diplomas and degrees, a balanced curriculum of core knowledge and competencies, technology, and teaching profiles. How to cite this article:  Rao NG, Selvakumar YS.A Study on the Impact of Globalization in the Field of Higher Education. J Adv Res Eng & Edu 2022; 7(3): 1-4. DOI: https://doi.org/10.24321/2456.4370.202204